Suboptimal treatment response to anti-IL-5 monoclonal antibodies in severe eosinophilic asthmatics with airway autoimmune phenomena. Issue 4 (8th October 2020) - Mukherjee, Manali; Forero, David Felipe; Tran, Stephanie; Boulay, Marie-Eve; Bertrand, Mylène; Bhalla, Anurag; Cherukat, Jayant; Al-Hayyan, Hajar; Ayoub, Anmar; Revill, Spencer D.; Javkar, Tanvi; Radford, Katherine; et al.
Background: In clinical trials, the two anti-interleukin (IL)-5 monoclonal antibodies (mAbs: mepolizumab and reslizumab) approved to treat severe eosinophilic asthma reduce exacerbations by ∼50–60%. Objective: To observe response to anti-IL-5 mAbs in a real-life clinical setting, and to evaluate predictors of suboptimal response. Methods: In four Canadian academic centres, predefined clinical end-points in 250 carefully characterised moderate-to-severe asthmatic patients were collected prospectively to assess response to the two anti-IL-5 mAbs. Suboptimal response was determined based on failure to reduce maintenance corticosteroid (MCS) or asthma symptoms scores (Asthma Control Questionnaire (ACQ)) or exacerbations, in addition to persistence of sputum/blood eosinophils. Worsening in suboptimal responders was assessed based on reduced lung function by 25% or increase in MCS/ACQ. A representative subset of 39 patients was evaluated for inflammatory mediators, autoantibodies and complement activation in sputum (by ELISA) and for immune-complex deposition by immunostaining formalin-fixed paraffin-embedded sputum plugs. Results: Suboptimal responses were observed in 42.8% (107 out of 250) patients treated with either mepolizumab or reslizumab. Daily prednisone requirement, sinus disease and late-onset asthma diagnoses were the strongest predictors of suboptimal response. Asthma worsened in 13.6% (34 out of 250) of these patients. The majority (79%) of them were prednisone-dependent. Presence of sputum anti-eosinophil peroxidase immunoglobulin (Ig)G was a predictor of suboptimal response to an anti-IL-5 mAb. An increase in sputum C3c (marker of complement activation) and deposition of C1q-bound/IL-5-bound IgG were observed in the sputa of those patients who worsened on therapy, suggesting an underlying autoimmune-mediated pathology. Conclusion: A significant number of patients who meet currently approved indications for anti-IL5 mAbs show suboptimal response to them in real-life clinical practice, particularly if they are on high doses of prednisone. Monitoring blood eosinophil count is not helpful to identify these patients. The concern of worsening of symptoms associated with immune-complex mediated complement activation in a small proportion of these patients highlights the relevance of recognising airway autoimmune phenomena and this requires further evaluation. Severe asthmatics with adult-onset asthma, sinus disease and requiring daily prednisone, are at higher risk for responding suboptimally to current doses of anti-IL-5 mAbs, with further risk of worsening on an IgG1 mAb if they have sputum autoantibodies https://bit.ly/2Ahpvsm